Bioleaching mechanism of Zn, Pb, In, Ag, Cd and As from Pb/Zn smelting slag by autotrophic bacteria. (15th August 2015) - Wang, Jia; Huang, Qifei; Li, Ting; Xin, Baoping; Chen, Shi; Guo, Xingming; Liu, Changhao; Li, Yuping
Abstract: A few studies have focused on release of valuable/toxic metals from Pb/Zn smelting slag by heterotrophic bioleaching using expensive yeast extract as an energy source. The high leaching cost greatly limits the practical potential of the method. In this work, autotrophic bioleaching using cheap sulfur or/and pyrite as energy matter was firstly applied to tackle the smelting slag and the bioleaching mechanisms were explained. The results indicated autotrophic bioleaching can solubilize valuable/toxic metals from slag, yielding maximum extraction efficiencies of 90% for Zn, 86% for Cd and 71% for In, although the extraction efficiencies of Pb, As and Ag were poor. The bioleaching performance of Zn, Cd and Pb was independent of leaching system, and leaching mechanism was acid dissolution. A maximum efficiency of 25% for As was achieved by acid dissolution in sulfursulfur oxidizing bacteria (S-SOB), but the formation of FeAsO4 reduced extraction efficiency in mixed energy source – mixed culture (MS-MC). Combined works of acid dissolution and Fe 3+ oxidation in MS-MC was responsible for the highest extraction efficiency of 71% for In. Ag was present in the slag as refractory AgPb4 (AsO4 )3 and AgFe2 S3, so extraction did not occur. Highlights: Autotrophic bioleaching was applied first to tackle the Pb/Zn smelting slag. Maximum extraction of 90% for Zn, 86% for Cd and 71% for In was obtained. Extraction of Zn, Cd and Pb was due to acid dissolution by biogenetic H + . Formation of FeAsO4 caused lower As extraction in MS-MC than in S-SOB. Acid dissolution and Fe 3+ oxidation caused highest extraction of In by MS-MC.